Analisis Literatur : Efektivitas Bahan Aktif Berbasis Herbal Pada Hair Tonic untuk Perawatan Rambut Rontok - Bethanyestha Rosshelia; Azzahra Alya Putri; Dewi Novita Panggabean; Saqina Anggelina Akhyar; Jessi Eratika Putri Radian; Setianingrum Setianingrum; Ratna Nur Yunida; Eny Widhia Agustin; Indah Indi Afifah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Hair loss is one of the most common problems in cosmetology, with significant impacts on both the aesthetic and psychological aspects of individuals. As public preference for natural based products continues to rise, herbal cosmetics particularly hair tonic formulations have become increasingly popular as alternative hair care solutions. This study aims to evaluate the effectiveness of several commonly used herbal active ingredients in hair tonic products, namely Aloe vera, ginseng, and candlenut (Aleurites moluccanus), in stimulating hair growth. The method employed is a literature review of relevant national and international scientific publications. The analysis indicates that ginseng at a concentration of 6% demonstrates the highest effectiveness in promoting hair growth, achieving a length of 17.7 mm within 14 days. Candlenut at a 20% concentration shows hair growth of 9.46 mm in 12 days, while Aloe vera at a 5% concentration exhibits a lower growth effect compared to the other two ingredients. Based on these findings, it can be concluded that ginseng is the most effective and promising active ingredient for use in herbal-based hair tonic formulations to address hair loss.